(untitled) (Namibian Journal for Research, Science and Technology, 2022)
Stated preference experiments are become an increasingly popular survey methodology for investigating air traveler’s choices. Analysis of this behaviour, which is an element of the demand prediction, helps for a better future planning and development of competing airlines. In this paper, emphasis is stressed on the stated preferences of passengers in choosing between low cost carriers (LCC) and full service carriers (FSC). A binary logit, probit and latent class models were employed on the primary data collected from departing air passengers at Eros and Hosea Kotako International airport in Windhoek, Namibia, to model passengers’ stated preferences and examine the determinants of carrier choice between LCC and FSC in Namibia. Major findings show that airfare, age, income, and purpose of travel are significantly important with respect to passenger choice. Furthermore, it was observed that passengers have different preferences for different destination region be it domestic, regional and international. For domestic and regional flights (short haul) they prefer LCC, while for international flights (long haul) they opted for FSC. In addition, majority of the passengers were travelling for business purposes, hence their tickets were bought by their respective employers. Most passengers indicated that they were willing to fly LCC if it was available in Namibia because of it’s low fares. There was an indication that air tickets were not affordable and these are a big concern to passengers. Presumably, if ticket prices can come down or introduce a LCC in Namibia then many consider flying. This study concluded that, based on the interviewed passengers’ profiles, the best and appropriate carrier in Namibia is a low-cost carrier. Introducing a LCC in Namibia might be a viable alternative which may ensure sustainability.